Proliferative verrucous leukoplakia and its tumor markers: Systematic review and meta-analysis - Mirjami Rintala; Tero Vahlberg; Tuula Salo; Jaana Rautava (John Wiley and Sons Inc., 2022)
Background: The aim was to update information on oral proliferative verrucous leukoplakia (PVL), a disease of verrucous‐like lesions with high risk of malignancy, and its biomarkers.
Methods: A systematic search of literature on PVL and its biomarkers showed 22 biomarkers that were investigated in 19 papers. A meta‐analysis was possible for human papillomavirus (HPV), aneuploidy, Ki‐67, and p53.
Results: Aneuploidy was found consistently (I2 = 0%, P = 0.61) in 92% (95% CI 80%‐99%) of the PVL cases. P53 positivity prevalence was 27% (95% CI 15%‐40%) in two available studies (I2 = 0%, P = 0.64). With HPV and Ki‐67, the most outlying studies needed to be removed and after that the pooled HPV positivity prevalence (I2 = 24%, P = 0.27) was 5% (95% CI 0%‐14%) and for Ki‐67 (I2 = 9%, P = 0.33) 14% (95% CI 6%‐26%).
Conclusions: With the evidence of the current literature, aneuploidy could value as a biomarker of PVL but should be further validated.